P-389 Elevated BMI in oocyte donors or recipients is associated with a higher risk of miscarriage after blastocyst transfer: a multicenter analysis of 1544 procedures. (30th June 2022) - Fabozzi, G; Cimadomo, D; Maggiulli, R; Badajoz, V; Aura Masip, M; Bongioanni, F; Benini, F; Degl'Innocenti, A; Buffo, L; Hebles Duvison, M; Sànchez Martìn, F; Sànchez Martìn, P; et al.
Abstract: Study question: Is an elevated BMI in either oocyte donors or recipients associated with a higher risk of miscarriage after blastocyst transfer? Summary answer: Overweight in oocyte donors and/or obesity in recipients are associated with a 2X-higher risk of miscarriage in egg donation cycles. What is known already: Several basic-science, clinical and epidemiological studies revealed an association between BMI and infertility, suggesting a J-shaped relationship: both underweight and especially overweight/obese women can suffer from reproductive impairments. In particular, overweight-obese women are more prone to suffer from a miscarriage even when euploid blastocysts are transferred. Yet, it is still unclear whether this is the consequence of an altered oocyte (and then embryonic) competence and/or an impaired endometrial receptivity. In this context, oocyte donation cycles represent the ideal clinical setting to shed some light on an issue with numerous social, clinical, and logistic implications. Study design, size, duration: Retrospective study including 1544 blastocyst single embryo transfers (SETs) conducted in oocyte donation cycles (Jan2019-May2021). All oocytes were vitrified at 2 egg banks in Spain and warmed at 8 clinics part of the same network. The primary outcome was the miscarriage rate (<22 nd gestational weeks) per clinical pregnancy according to donors' and/or recipients' BMI. Four BMI clusters were defined (underweight: <18.5; normal-weight: 18.5-24.9; over-weight: 25-30; obese: >30). Participants/materials, setting, methods: 66.1%, 4.9%, 20.3% and 8.7% of SETs were conducted in normal-weight, underweight, overweight, and obese recipients. 81.4%, 4.5% and 14.1% of SETs with oocytes derived from normal-weight, underweight, and overweight donors. The putative confounders investigated were egg bank, IVF center, fresh/vitrified-warmed SET, blastocyst quality/day, recipient/donor age, endometrial preparation protocol, number of consecutive SET. Before SET, we requested blood test for infections and TORCH, thyroid function, coagulation and immunological assessment, cardiological, gynecologic and breast evaluation. Main results and the role of chance: Overweight-obese recipients were slightly older (43.0±4.0yr) than normal-weight ones (42.2±3.8yr; p < 0.01). Similarly, overweight donors were slightly older (27.5±4.5yr) than normal-weight ones (26.4±4.3yr; p < 0.01). Therefore, all outcomes were adjusted for recipients'/donors' age. The overall positive pregnancy rate per blastocyst SET and biochemical pregnancy loss rate were 51.8% and 12.6%. No association was reported between either recipients' or donors' BMI and both these secondary outcomes. Conversely, higher recipients' and donors' BMI were significantly associated with a higher risk of miscarriage after blastocyst SET (multivariate-OR 1.05, 95%CI 1.01-1.1, adjusted-p=0.05; multivariate-OR 1.1, 95%CI 1.04-1.2, adjusted-p<0.01). The most significant differences were reported for obese versus normal-weight recipients (N = 18/64, 28.1% versus N = 73/448, 16.3%; p = 0.03, power=60%; multivariate-OR 1.8, 95%CI 1.01-3.4, adjusted-p=0.05) and for overweight versus normo-weight donors (N = 31/111, 27.9% versus N = 94/561, 16.8%; p < 0.01, power=73%; multivariate-OR 1.9, 95%CI 1.16-3.0, adjusted-p=0.01). In the 14 clinical pregnancies where the oocytes derived from overweight donors and the blastocysts were transferred to obese women the miscarriage rate was 50%; the same outcome in normal-weight recipients using oocytes from normal-weight donors was 15% (N = 55/366; p < 0.01, power=85%; OR 5.6, 95%CI 1.8-16.8, p < 0.01). The data were similar across both egg banks and all IVF centers. All other parameters assessed were not associated with the primary outcome under investigation. Limitations, reasons for caution: The study is retrospective, and the sample size in each sub-group shall be increased. Moreover, BMI is a gross marker of an individual's metabolic status. Future studies on more accurate markers like percentage and localization of adipose tissue assessed through techniques like bioelectrical impedance analyses are desirable. Wider implications of the findings: Both oocyte competence and endometrial receptivity might be impaired from unbalanced nutritional intakes. More studies on this topic are certainly required. Whenever possible, nutritional/lifestyle adjustments should be encouraged in obese patients because of their higher risk of miscarriage, and a BMI limit should be considered also when recruiting egg donors. Trial registration number: Not applicable